2019
DOI: 10.1177/2150132719884838
|View full text |Cite
|
Sign up to set email alerts
|

Medical Cannabis for the Primary Care Physician

Abstract: Medical cannabis use is common in the United States and increasingly more socially acceptable. As more patients seek out and acquire medical cannabis, primary care physicians will be faced with a growing number of patients seeking information on the indications, efficacy, and safety of medical cannabis. We present a case of a patient with several chronic health conditions who asks her primary care provider whether she should try medical cannabis. We provide a review of the pharmacology of medical cannabis, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Recent articles also attempt to close this knowledge gap. 23 In addition, it is important to include cannabis education in health professions curricula to expose students to this topic during their training. A 2017 study demonstrated that only 9% of medical schools currently have medical cannabis included in their curricula.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent articles also attempt to close this knowledge gap. 23 In addition, it is important to include cannabis education in health professions curricula to expose students to this topic during their training. A 2017 study demonstrated that only 9% of medical schools currently have medical cannabis included in their curricula.…”
Section: Discussionmentioning
confidence: 99%
“…Recent articles also attempt to close this knowledge gap. 23 In addition, it is important to include cannabis education in health professions curricula to expose students to this topic during their training. A 2017 study demonstrated that only 9% of The N for each condition varies depending on self-reported data about having the listed condition and having tried CBD or THC as a treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As MC becomes more socially acceptable [ 21 ], new physicians will encounter a growing number of patients looking for information on its utility and safety. [ 22 ]. Moreover, medical students tend to be young, and young adults may hold more permissive opinions about cannabis [ 23 ] and perceive it to be less harmful than their older counterparts [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In April 2022, the United States House of Representatives passed legislation that attempts to legalize cannabis at the federal level [19]. In this context, early-career physicians will most likely come across patients asking for information on MC's usefulness and safety as it becomes more socially acceptable [20,21], and legalization continues to expand. In light of these recent events, MC may likely become a significant issue for the healthcare profession and medical trainees in particular who might be expected to inform patients of its efficacy, recommend it, and develop treatment plans.…”
Section: Introductionmentioning
confidence: 99%
“…As MC increases its social acceptability [20] and laws begin to change in favor of legalization, newly trained physicians will be faced with an increased number of patients looking for treatment options and information on the safety of medical cannabis [21]. To date, however, there are few if any, instruments available that can measure students' perceptions of MC, including concerns and willingness to use MC in their post-residency practice.…”
Section: Introductionmentioning
confidence: 99%